Nutrition Practice and Knowledge of First-Year Medical Students. (27th August 2017) - Perlstein, Robyn; McCoombe, Scott; Macfarlane, Susie; Bell, Andrew Colin; Nowson, Caryl
Abstract : Objectives . To compare the knowledge of Australian dietary recommendations to the dietary practices of first-year medical students. Design . Over a period of four years, anonymous online surveys were completed by medical students attending a first-year nutrition lecture. Background . There is little information on the nutritional knowledge and dietary practices of medical students. Setting . First-year postgraduate university medical students, Geelong, Victoria, Australia. Participants . Between the years 2012 and 2016, 32%–61% of first-year students completed the survey. Phenomenon of Interest . Student's knowledge of dietary guidelines and related practices. Analysis . The frequency of response was assessed across the different year cohorts using descriptive statistics. Results . Between 59% and 93% of first-year students correctly identified the recommended daily servings for fruit, and between 61% and 84% knew the vegetable recommendations. In contrast only 40%–46% met the guidelines for fruit and 12%–19% met the guidelines for vegetables. Conclusions and Implications . Discrepancies between students' nutrition knowledge and behavior can provide learning opportunities. With low rates of fruit and vegetable consumption in medical students, increased awareness of links between nutrition and health, together with encouragement to make behavioral changes, may increase the skills of graduates to support patients in improving dietary intake.